Damaskin Semenov-Rudnev: Philosopher and Panegyricist - Drozdek, Adam (Slavica, 2018)
The article provides a short summary of the philosophical and theological views of Damaskin Semenov-Rudnev, an 18th century Russian clerical leader, on the basis of his philosophical theses and sermons. The article also shows that his theology served as a means for consolidating the imperial power of Catherine II.